2004
DOI: 10.1136/bjo.2003.028340
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Ro/SSA and anti-La/SSB autoantibodies in the tear fluid of patients with Sjogren's syndrome

Abstract: Purpose: To investigate the presence of anti-Ro/SSA and anti-La/SSB antibodies in the tear fluid and serum of patients with Sjögren's syndrome and to evaluate the association of these autoantibodies with the severity of keratoconjunctivitis sicca. Methods: Tear fluid and serum were obtained from 28 patients with Sjögren's syndrome and 17 age matched normal control subjects. Evaluation of tear fluid and sera anti-Ro/SSA and anti-La/SSB levels was done by using a quantitative enzyme linked immunosorbent assay ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 30 publications
1
36
0
2
Order By: Relevance
“…In fact, we found increased BAFF levels in tear fluid in patients with pSS compared to healthy subjects, and we also observed significant difference between on and off HCQ treatment in pSS itself. We previously showed that autoantibodies such as anti-Ro, anti-La, IgG-and IgA-a fodrin could be detected in tear fluid even, when there are not present in the serum of patients with pSS [23,24]. Therefore, it may be plausible to think that BAFF may contribute local autoantibody production or persistence of B cells in inflammatory environment of dry eye.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, we found increased BAFF levels in tear fluid in patients with pSS compared to healthy subjects, and we also observed significant difference between on and off HCQ treatment in pSS itself. We previously showed that autoantibodies such as anti-Ro, anti-La, IgG-and IgA-a fodrin could be detected in tear fluid even, when there are not present in the serum of patients with pSS [23,24]. Therefore, it may be plausible to think that BAFF may contribute local autoantibody production or persistence of B cells in inflammatory environment of dry eye.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies also correlated anti-Ro/La antibody positivity to recurrent or permanent parotid gland enlargement [5,22,34] decreased salivary flow [22], more intense symptoms from the eyes, worse Schirmer test and Rose Bengal staining scores [36] and positive salivary gland biopsy [5]. In pSS the degree of labial salivary gland infiltration [37], as well as the development of germinal centre like structures [38] has been associated with the presence of anti-Ro/SSA and anti-La/SSB antibodies.…”
Section: Clinical Implications Of Anti-ro/ssa and Anti-la/ssb In Sjögmentioning
confidence: 99%
“…2 In 2012, the American College of Rheumatology published a classification system for primary SS that used autoantibodies such as antinuclear antibody (ANA), Sjögren syndrome A (SSA)/Ro antibody, Sjögren syndrome B (SSB)/ La antibody, and rheumatoid factor (RF). 3 Although anti-Ro/ SSA and anti-La/SSB antibodies have been found in salivary glands 4,5 and tears, 6 the contribution of autoantibodies to dry eye pathogenesis remains unclear.…”
mentioning
confidence: 99%